Gemcitabine Delivery and Photodynamic Therapy in Cancer Cells via Porphyrin‐Ethylene‐Based Periodic Mesoporous Organosilica Nanoparticles. Issue 1 (4th October 2017) - Aggad, Dina; Jimenez, Chiara Mauriello; Dib, Soraya; Croissant, Jonas G.; Lichon, Laure; Laurencin, Danielle; Richeter, Sébastien; Maynadier, Marie; Alsaiari, Shahad K.; Boufatit, Makhlouf; Raehm, Laurence; Garcia, Marcel; et al.
Abstract: Gemcitabine hydrochloride is an FDA‐approved chemotherapeutic drug used in the treatment of various cancers. Several drawbacks of gemcitabine, including its short in vivo half‐life of 8–17 min associated with a rapid excretion by the kidneys and its poor membrane permeability, have inspired research on a nanodelivery approach. In this study, we report ethylene‐based periodic mesoporous organosilica nanoparticles (PMOs) for photodynamic therapy and the autonomous delivery of gemcitabine in cancer cells. Porphyrins were used as photosensitizers and were localized in the walls of the PMOs while a high loading capacity of gemcitabine was observed in the porous structure. Depending on the nature of the photosensitizer, and its aggregation state, we were able to perform one or two‐photon photodynamic therapy. Two‐photon excited photodynamic therapy combined with gemcitabine delivery led to a synergy and a very efficient cancer cell killing. Abstract : Gemcitabine delivery in cancer cells was studied with mesoporous organosilica nanoparticles engineered for photodynamic therapy. Two‐photon photodynamic therapy combined with gemcitabine delivery led to a synergy and a very efficient cancer cell killing.